Research Output and Impact in Data Science and Informetrics: A Bibliometric Study of JDSICS (2022–2024) - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies)
This study presents a comprehensive bibliometric analysis of the Journal of Data Science, Informetrics, and Citation Studies (JDSICS) over the period 2022–2024. Using data collected from the journal's official website and verified through bibliographic databases, Google Scholar. A total of 57 research articles were examined across key indicators, including publication trends, authorship patterns, institutional affiliations, geographic distribution, major themes, and keyword usage. The results reveal a steady growth in publication output, with a significant increase in both the number of issues and articles published annually. Collaborative research dominates the authorship landscape, with two-author contributions being most frequent. India emerged as the leading contributor, accounting for over 85% of the total publications, followed by limited contributions from Pakistan, Iran, and Malaysia. Thematic analysis highlights bibliometrics, scientometrics, and subject-specific research mapping as the most explored areas, while keyword frequency further confirms the journal's focus on scholarly communication and research evaluation. The study concludes that JDSICS is gaining momentum as a vital platform for researchers in data science, informetrics, and citation studies, while also encouraging broader international participation and interdisciplinary engagement.
Keywords: Bibliometrics; Data Science; Informetrics; Citation Studies; JDSICS; Scientometrics; Altmetrics; Research Output.